Mortality predictors in ANCA-associated vasculitis: Experience of a Brazilian monocentric cohort of a rheumatology center. Issue 51 (23rd December 2021) - Dagostin, Marilia A.; Nunes, Sergio L.O.; Shinjo, Samuel K.; Pereira, Rosa M.R.
Abstract : Abstract: The mortality rate of patients with anti-neutrophil cytoplasm antibody -associated vasculitis (AAV) is higher than the general population. To date, no studies have evaluated the factors associated with unfavorable outcomes in Brazilian patients, who represent a miscegenated population. Our objective was to identify clinical and laboratory features associated with mortality in Brazilian patients with AAV. One hundred twenty eight patients fulfilling the American College of Rheumatology and Chapel Hill Classification Criteria followed between 2000 and 2018 in our Rheumatology Outpatient Clinics were included. Data were obtained from an ongoing electronic database. Patients were divided into 2 groups (dead or alive in 2018), and disease activity (Birmingham vasculitis activity score [BVAS]), vasculitis-related damage (VDI), and laboratory parameters were compared at the most recent attendance and at the last attendance before death. Of the 128 patients followed, 78.9% had granulomatosis with polyangiitis, 16.4% had eosinophilic granulomatosis with polyangiitis, and 4.6% had microscopic polyangiitis. In 2018, 78 patients were alive, 25 had died, and 25 had lost contact. The main cause of death was infection. According to the univariate analysis, the Birmingham vasculitis activity score, VDI, and glucocorticoid dose were higher in the group of patients who died. Laboratorial features related to mortality were creatinine, hemoglobin, erythrocyte sedimentation ratio, and C-reactive protein (CRP). Logistic regression analysis showed that high VDI, creatinine levels, and CRP levels were independent factors associated with mortality. Survival was significantly decreased in patients with renal impairment. This is the first study to use this approach performed in a Brazilian population and it showed that damage index, renal impairment, and CRP levels were associated with mortality in a miscegenated population with AAV.